Mempersuasi Dan Menumbuhkan Motivasi Siswa Untuk Melanjutkan Pendidikan Ke Tingkat Perguruan Tinggi - Alfiyaty, Rizqy; Adrian, Donal; Fadhliah, Fadhliah; Yusaputra, Muhammad Isa; Mahardika, I Putu Agus Eka Jaya; Asiyah, Rihadatul; Samsiar, Samsiar; Rahma, Syafina Aulia (Universitas Pahlawan Tuanku Tambusai, 2024)
Every Indonesian citizen has the right to receive education up to university level. The right to receive education is one of the human rights stated in CHAPTER XIII on Education and Culture in the 1945 Constitution after the amendment, namely Article 28 paragraph (1) which states